Pengaruh Kelompok Rujukan, Gaya Hidup Dan Kontrol Diri Terhadap Perilaku Konsumtif Pengguna Aplikasi Shopee (Studi Kasus pada Mahasiswa FEB UNISMA Angkatan 2021) - Tantri, Diah Ima Novia; Hidayati, Nur; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze and explain the effect of reference groups, lifestyle and self-control on the consumptive behavior if Shopee application users. The population of this study were students of the faculty of business economics, poor Islamic university class of 2021. The sampling technique used Snowball sampling with the Slovin formula and obtained 87 respondents. The method of data analysis in this study is quantitative data analysis using multiple linear regression analysis with the help of SPSS. The results showed that lifestyle variables had an effect on the consumptive behaviour of Shopee application users, while reference groups and self-control had no effect on the consumptive behaviour of Shopee application users. Keywords: Reference Group, Lifestyle, Self-Control and Consumptive Behavior